Unconducting the Self-Synchronizing Orchestra - Culver, Andrew (Circuit)

(untitled) (Les Presses de l’Université de Montréal, 2012)
Synchronization is the science of the mutual influence of oscillating systems. Although the term is commonly misused as a synonym for unification, it is a far richer concept in its true, organic sense. There is a burgeoning body of research on synchronization in many fields of science. This article notes some important new forms of human interaction where the precepts of synchronization provide a novel and useful framework for analysis and understanding. Orchestral music is one of them. As the nature and means of our communications evolve, we become experienced in new patterns of interaction, which require of us new methods of composition and performance that make us feel more in harmony with the way we have become. Synchronization provides a science-based description of non-causal, non-hierarchical influence mechanisms that work, at the cellular, human, and ecosystem level.